Nivolumab-induced interstitial lung disease in the patient with melanoma - Morawski, Marcin; Trąd, Gabriela; Gawlewicz-Mroczka, Agnieszka (Alergologia Polska - Polish Journal of Allergology, 2025)
This article presents the case of a drug-induced interstitial lung disease in response to nivolumab, which is a programmed death receptor 1 (PD1) blocking antibody. A 66 year-old-man with metastatic melanoma of the scalp was treated with monthly nivolumab infusions at a dose of 480 mg. After 23 doses of nivolumab the patient had follow-up high-resolution computed tomography which revealed interstitial reticular changes. The administration of the drug was stopped and the patient was admitted to the Pulmonology and Allergology Department. Bronchoscopy was performed. Infectious background of radiological findings was excluded, the bronchoalveolar lavage fluid showed dominant lymphocytes. The patient started methylprednisolone therapy with a gradually tapered dose. Chest computed tomography after 1 month of treatment showed significant improvement. The administration of high-dose corticosteroid is recommended after the diagnosis of the drug-related adverse reaction in new generation immunology treatment. Resuming nivolumab treatment is possible in some cases, after toxicity has sufficiently resolved and only after a specialist’s assessment. In this patient oncology treatment was terminated.